RELATIONSHIP BETWEEN FIVE DIMENSION OF JOB CHARACTERISTIC MODEL WITH JOB STRESS - Yasica Dyah Pramesthi (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2018)
This study aims to analyze the relationship between five job characteristic model dimension and job stress on insurance agents. The sample used in this research is agents of AsuransiJiwaBersamaBumiputera in Solo Raya with the number of respondents as many as 97 agents.The data retrieved by using purposive sampling. Tests in this study using the test instrument in the form of validity test with Confirmatory Factor Analysis (CFA) method and reliability test by Cronbach’s Alpha method. Hipotesis test using Multiple Regreesion Analysis method.The result of this research suggest that all of five dimension job characteristic model does not entirely have negative relationship and is not significant to job stress. Skill variety has positive relation with job stress, task identity and task significance have negative relation with job stress, autonomy and feedback have not significant relationship with job stress. This study has limitations that most of the questionnaires distributed are not given directly to the research subjects, but deposited in each division head or section head so as to increase the likelihood of bias. Keywords : skill variety, task identity, task significance, autonomy, feedback, job stress.